Oral National Creativity in a Communication System (Fragmentary Analysis) (Herald of Journalism, 2019)
In the era of the development of the information society, communications are considered not only as technological means of communication, communication between living beings or as effective synchronous and diachronic interaction, the purpose of which is to transfer information from one subject to another, but also as a communication process that is the object and subject of scientific analysis. Thus, composing the science of communication science, whose functions are to study the so-called meta discourse about the social process of “communication / interaction / interaction”, in order to get this process itself, its results and ensure efficiency. In Kazakhstan’s practice, in the conditions of independent development of the state, social communicative institutions are practically formed; a scientific approach to analyzing the content of informational and communicative events, their effectiveness, and effectiveness is actualized in connection with the specifics of the formation of statehood and national identity. In the conditions of the formation of Kazakh statehood, such concepts as ethnic unity, honor, justice, tolerance, endurance, patriotism, generic, etc., acted as a value meaning for the people. All the Kazakh zhyrau of that time sang in their poems and poems of the batyrs, who fought for their native land, gave them due for their courage, heroism, and justice. Here we see elements of both political communication and image, social, etc. It was oral folk art that was a means of communication of different generations, it bore the burden of a unique institution of spirituality and morality. The technology of oral communication is based on the direct-contact type of interaction, the elementary cell of which is the direct transfer of the message “from hand to hand”, from the sender to the addressee, without any technical intermediary between them, which enhances the emotional impact and, accordingly, its effectiveness. The purpose of the article is to consider the main aspects of the study of folk tradition as the primary form of cultural communication. This scientific publication attempts to substantiate the concept of the origin of communicative interaction as the basic basis for the development of Kazakhstan’s statehood.
Keywords: communication, information, communication platform, poet, communicator, public relations.